Internal and external export barriers: analysis from Serbian SMEs point of view - Sudarevic, Tomislav; Radojevic, Predrag (Industrija, 2014)
Influence of enterprise characteristics, i.e. size, length of export experience, capital ownership and type of industry, on export barriers perception in case of Serbian manufacturing SMEs exporters was researched in this paper. Aims of the study were to identify factors that may pose export barriers for Serbian SMEs, rank perceived barriers, spotting differences by different groups of SMEs, and examine correlations between SMEs characteristics and export barriers perception. Main hypothesis was that SMEs from Serbia perceive factors that may pose export barriers similar to exporters in other countries, but degree and magnitude of influence depend on enterprise's characteristics. The empirical research has been conducted through a survey and 137 exporters taking part in it, which gave response rate of 35.49%. For collected data processing and analyzing descriptive statistics, differences among groups and correlation tests were employed. Results showed that influences of the enterprise size and foreign capital ownership on export barriers perception are positive, which means that small and domestic enterprises face larger barriers to export compared to medium and foreign ones